PENGARUH DEBT TO TOTAL ASSET RATIO TERHADAP RETURN ON EQUITY DAN MANFAAT EKONOMI ANGGOTA - Eka Setiajatnika; Muhamad Ardi Nupi, Hasyim; Risma, Oktavira (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
One of the important decisions faced by cooperatives is the decision on capital structure, namely financialdecisions relating to the composition of debt. How much the use of debt can improve services in theCooperative business unit and how much the use of debt can produce optimal profits. The method used inthis research is the case study method, which is a research method by collecting data and direct observationof the object under study in order to find out and understand the solution of problems in the BJB BankEmployees Cooperative "ZIEBAR". Debt to Total Asset Ratio (DAR) to Return on Equity (ROE) has a verystrong and negative relationship. There is it can be said that if the Debt to Total Asset Ratio (DAR)increases, the level of Return on Equity (ROE) will decrease as well as if the Debt to Total Asset Ratio(DAR) has decreased, the level of Return on Equity (ROE) will experience enhancement. Based on Returnon Equity (ROE) data which always decreases and debt that always increases from year to year, it meansthat the BJB Bank Employee Cooperative "ZIEBAR" has bigger debt but does not make Return on Equity(ROE) even greater. The Influence of Debt to Total Asset Ratio (DAR) on Economic Benefits Members havemoderate and negative relationships. There is it can be said that if the Debt to Total Asset Ratio (DAR)increases, the Member's Economic Benefits will decrease as well as if the Debt to Total Asset Ratio (DAR)has decreased, the Member's Economic Benefits will increase. Based on the data of the Economic Benefitsof Members which are always increasing and the debt has also increased, it can be said that the BJBEmployee Cooperative "ZIEBAR" has provided Member Economic Benefits.